2011
DOI: 10.1098/rsbl.2011.0975
|View full text |Cite
|
Sign up to set email alerts
|

Wild geese do not increase flight behaviour prior to migration

Abstract: Hypertrophy of the flight muscles is regularly observed in birds prior to long-distance migrations. We tested the hypothesis that a large migratory bird would increase flight behaviour prior to migration, in order to cause hypertrophy of the flight muscles, and upregulate key components of the aerobic metabolic pathways. Implantable data loggers were used to record year-round heart rate in six wild barnacle geese (Branta leucopsis), and the amount of time spent in flight each day was identified. Time in flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
(47 reference statements)
0
20
0
Order By: Relevance
“…Few studies have investigated the pre-migratory stage in birds (Fliege 1984, Van der Winden et al 2010, Portugal et al 2012, and particularly in colonial raptors (but see Limiñana et al 2008). Summer concentrations of Lesser Kestrels were documented in Northern Spain (Olea 2001, Olea et al 2004), but we have found them as a broad phenomenon occurring across the species' Southern European range (cf.…”
Section: Discussionmentioning
confidence: 92%
“…Few studies have investigated the pre-migratory stage in birds (Fliege 1984, Van der Winden et al 2010, Portugal et al 2012, and particularly in colonial raptors (but see Limiñana et al 2008). Summer concentrations of Lesser Kestrels were documented in Northern Spain (Olea 2001, Olea et al 2004), but we have found them as a broad phenomenon occurring across the species' Southern European range (cf.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, despite being visually guided foragers, it is very unlikely the geese are waking up to forage on moonlit nights, as there is little to no food available to them in the immediate vicinity of their roosts. Furthermore, unlike T ab , f H does not show such an extreme increase during perigee events as to nearly match daytime f H activity levels (Portugal, Green, & Butler, ; Portugal et al, , ; Figure ). This small degree of increase in f H compared to flight confirms that it is unlikely that the birds are becoming active or moving extensively since even small regular movements are typically accompanied by increases in heart rate (Butler, Green, Boyd, & Speakman, ).…”
Section: Discussionmentioning
confidence: 94%
“…The mass of the internally implanted device (21 g) was comfortably below the 5% of total body mass recommended when deploying internally implanted biologging devices on birds (Portugal & White, 2018;White et al, 2013). Mean daily heart rate of all geese was used to determine daily activity levels (see Portugal, Green, White, Guillemette, & Butler, 2012), in order to identify the autumn migratory flights taking place in September, from Svalbard to Scotland. Nighttime mean T ab and f H were calculated on an individual basis as the mean between 23:00 and 03:00.…”
Section: Body Temperature and Heart Rate Measurementsmentioning
confidence: 99%
“…However, the relationship between a c tiv ity /, and m in im u m /H for Australasian gannets is significantly negative. This is a product of the curvilinear relationship between V02 and fH (Green et al 2013) and the greater proportion of the day spent in flight by this species (25%-35%; Green et al 2013) compared to the other volant bird species included in this study (usually <5%;Gremillet et al 2005;Pelletier et al 2008;Portugal et al 2012). For any species, a curvilinear relationship results in the difference in heart rate between m inim um fH and mean / H, equating to a greater A 0 50 100 150 200…”
Section: Appendix Qualitative Analysis Of Metabolic Rates In Birdsmentioning
confidence: 99%